ANALISIS PENGENDALIAN CACAT PRODUK TELUR AYAM MENGGUNAKAN STATISTICAL QUALITY CONTROL DI BRAM FARM - EVA KOSASIH; ALEN VIKTORIA BRIA; NI NYOMAN AYU NIRMALA LUKITA; NI PUTU SINTYA ARTA DEWI; MADE AYU DWI OCTAVANNY (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
This study aims to analyze the quality control of chicken egg production at Bram Farm by applying Statistical Quality Control (SQC) tools to identify the level and types of defects that occur during the production process. Quantitative data were obtained from primary documentation through daily records collected over a 14-day observation period, consisting of the total number of eggs produced and the number of defective eggs categorized into specific defect types. Qualitative data were collected through direct observations and unstructured interviews with the farm owner to validate statistical findings and explore operational factors causing defects. The analysis employs three main SQC tools: the check sheet to record defect occurrences, the Pareto diagram to identify dominant defect categories, and the p-chart to evaluate the statistical stability of the production process. The results show that cracked eggs, thin-shelled eggs, and broken eggs are the dominant defects contributing to the overall defect rate. The p-chart indicates that all daily defect proportions fall within the control limits, demonstrating that the production process was statistically stable. These findings suggest that quality control at Bram Farm is effective, although improvement efforts should focus on the dominant defect categories to enhance production quality further.